CORRELATION BETWEEN THE NUTRITIONAL STATUS OF PREGNANT WOMEN WITH STUNTING BABIES 6-24 MONTHS OLD IN THE WORKING AREA OF PASREPAN HEALTH CENTER - Buon, Jonathan Overian; Budipramana, Edwin; Rihadi, Lukas Slamet (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Stunting is a condition of impaired growth that children experience because of prolonged poor nutrition. Factors that cause stunting are the nutrition status of pre-pregnancy mothers, nutrition status during pregnancy, early initiation of breastfeeding, exclusive breastfeeding, environment sanitation, and infection in children. Stunting has an impact on suboptimal intelligence in children and also can result in a poor immune system. Objective: To know the correlation between pregnant mothers' nutrition status with stunting babies 6-24 months old in the working area of Puskesmas Pasrepan. Method: This study was an observational analytical study with a case-control retrospective design, participated by 80 babies which 40 were stunted and the other 40 were normal height and was taken from Pasrepan Health Center secondary data using consecutive technique sampling. Data was taken from Puskesmas Pasrepan consisted of mid-upper arm circumference (MUAC) of pregnant women, the height of children 6-24 months, age of children, number of ANC visits, and sex of children. Variables were analyzed using Chi-Square to know the correlation between the nutritional status of pregnant women with stunting. Results: 5 out of 6 stunted 6-24 months old babies (83,3%) were from malnourished pregnant women or maternal chronic energy deficiency (CED), and 35 out of 40 stunted 6-24 months old babies (47,3%) were from maternal with normal nutrition. The correlation between the nutritional status of pregnant women with stunting results was (p=0,09). Conclusion: There is no significant correlation between the nutritional status of pregnant women with stunting babies 6-24 months old.